Deterministic and probabilistic spectrums for the evaluation of seismic hazard in structures of the Tacna region - Ancco Huanacuni, Ever Rudy (2020)
The present study has the purpose of providing technical criteria to determine the seismic hazard in the Tacna region through deterministic and probabilistic elastic spectra that, consequently, may represent the seismic threat related to said region. This study considered earthquakes have been instrumentally recorded from 1965 to May 22, 2018, comprised in southern Peru and northern Chile. The main source of information is the seismic catalogs issued by the United States Geological Survey (USGS). The results reflect how it is the attenuation of these seismic events of a certain magnitude at a certain distance, based on a deterministic and / or probabilistic analysis, in which case the latter is extrapolated to a certain annual